A Fast Self‐Powered Solar‐Blind Ultraviolet Photodetector Realized by Ga2O3/GaN PIN Heterojunction with a Fully Depleted Active Region. Issue 8 (19th February 2023) - Chen, Wencheng; Xu, Xiangyu; Li, Minghang; Kuang, Siliang; Zhang, Kelvin H. L.; Cheng, Qijin
Abstract: Ga2 O3 is a wide bandgap semiconductor suitable for solar‐blind photodetection, but there exist two issues for Ga2 O3 ‐based photodetectors: first, it is difficult to achieve reliable p‐type Ga2 O3 and therefore form a homojunction photodetector, and the other is related with the slow response speed of Ga2 O3 ‐based photodetectors. In this work, a self‐powered solar‐blind photodetector with a fast response using a p‐GaN/i‐Ga2 O3 /n‐Ga2 O3 (pin) heterojunction with a fully depleted active region is realized, where i‐Ga2 O3 serves as the main light‐absorbing active region. The device exhibits good self‐powered characteristics with a high responsivity of 72 mA W −1, a high photo‐to‐dark current ratio of 18 800, a high specific detectivity of 3.22 × 10 12  Jones, and a fast response speed with a rise time/decay time of 7 ms/19 ms, respectively, without an external power supply. A detailed study of the interfacial electronic structure between p‐GaN and i‐Ga2 O3 reveals a conduction band offset and valence band offset of 0.16 and 1.37 eV, respectively. Meanwhile, it has a large built‐in potential of 1.03 eV and a wide depletion region width of 235 nm in the i‐Ga2 O3 side of heterojunction. It is believed that excellent device performance comes from a suitable energy band structure and wide depletion region. Abstract : A novel fabricated pin heterojunction photodetector with a fully depleted active region based on β‐Ga2 O3 and GaN exhibits good self‐powered characteristics with a high responsivity of 72 mA W −1, a high photo‐to‐dark current ratio of 18 800, a high specific detectivity of 3.22 × 10 12  Jones, and a fast response speed with a rise time/decay time of 7 ms/19 ms.